Triptolide Inhibits the Proliferation of HaCaT Cells Induced by IL22 via Upregulating miR-181b-5p - He Q; Zhang B; Hu F; Long J; Shi Q; Pi X; Chen H; Li J (Dove Medical Press, 2020)
Qi He,1,2,* Bo Zhang,1,2,* Feng Hu,3 Jianwen Long,1,2 Quan Shi,1,2 Xianming Pi,1,2 Hongxiang Chen,4 Jiawen Li4 1Department of Dermatology, Hubei Provincial Hospital of Traditional Chinese Medicine, Wuhan, Hubei 430061, People’s Republic of China; 2Department of Dermatology, Hubei Province Academy of Traditional Chinese Medicine, Wuhan, Hubei 430074, People’s Republic of China; 3Department of Dermatology, Wuhan No.1 Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, Hubei 430022, People’s Republic of China; 4Department of Dermatology, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, Hubei 430022, People’s Republic of China*These authors contributed equally to this workCorrespondence: Quan ShiDepartment of Dermatology, Hubei Provincial Hospital of Traditional Chinese Medicine, No. 4 Huanyuanshan, Wuchang District, Wuhan, Hubei 430061, People’s Republic of ChinaEmail shi_quan999@126.comBackground: Evidence has been shown that triptolide was effective in the treatment of psoriasis; however, the mechanisms remain poorly understood. Thus, this study aimed to investigate the role of triptolide on the proliferation and differentiation of HaCaT cells which are treated with IL22 to mimic abnormal proliferation/differentiation in keratinocyte of psoriasis.Materials and Methods: HaCaT cells were transfected with miR-181b-5p antagomir for 24 h, and then exposed to 10 μM Triptolide for 24 h, following by 100 ng/mL of IL22 for 24 h. In addition, the proliferation and cell cycle distribution in HaCaT cells were assessed by immunofluorescence or flow cytometry assays, respectively.Results: Triptolide obviously upregulated the level of miR-181b-5p in HaCaT cells. In addition, triptolide significantly inhibited IL22-induced proliferation of HaCaT cells via inducing cell cycle arrest. Moreover, IL22 markedly inhibited the differentiation of HaCaT cells, and this phenomenon was reversed by triptolide treatment. In contrast, the effects of triptolide on the proliferation and differentiation in IL22-stimulated HaCaT cells were notably reversed by miR-181b-5p antagomir. Moreover, dual-luciferase assay showed that E2F5 was the direct target of miR-181b-5p in HaCaT cells. Meanwhile, upregulation of miR-181b-5p obviously decreased the level of E2F5 in HaCaT cells.Conclusion: In this study, we found that triptolide could inhibit the proliferation and promote the differentiation in IL22-stimulated keratinocytes via upregulating miR-181b-5p. These data indicated that triptolide may be a potential agent for the treatment of psoriasis.Keywords: psoriasis, triptolide, keratinocytes, miR-181b, differentiation